MEKANISME PENGARUH CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP SALES GROWTH MELALUI TAX AGGRESIVITAS - Christnova Hasugian; Vebry M Lumban Gaol; Mangasa Sinurat; Annesa Adriyani; Nurkholik Nurkholik; Dokman Marulitua Situmorang (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to examine whether Capital Intensity and Inventory Intensity jointly influence sales growth and whether this influence is mediated by Tax Aggressiveness. The type of research used is quantitative research with an associative approach. The results of the study are The main findings indicate that simultaneously Capital Intensity and Inventory Intensity statistically significantly influence Sales Growth, although the explanatory power is low. The partial coefficient of Capital Intensity is negative and Inventory Intensity is positive, but both are not independently significant. Multicollinearity tests indicate no redundancy problem between Capital Intensity and Inventory Intensity. The interaction of Capital Intensity with Tax Aggressiveness and Inventory Intensity with Tax Aggressiveness is also not significant, so that aggressive taxation does not moderate the relationship between Capital Intensity or Inventory Intensity with sales growth. In short, Capital Intensity and Inventory Intensity do not independently influence Sales Growth in this specification, and Tax Aggressiveness does not act as a moderator.